VizieR Online Data Catalog: X-ray variability of M31 central field (Hofmann+, 2013) - Hofmann, F.; Pietsch, W.; Henze, M.; Haberl, F.; Strum, R.; Della Valle, M.; Hartmann, D. H.; Hatzidimitriou, D. (2013)
For all Chandra HRC-I observations a source catalogue was created and the energy flux of each source in each observation was derived. Fluxes were calculated assuming a generic power law spectrum and Galactic foreground absorption for each source. (5 data files).
Keywords: Binaries: X-ray; X-ray sources